2014
DOI: 10.1016/j.jadohealth.2013.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Trajectories of Substance Use Among Sexual Minority Girls: Associations With Sexual Victimization and Sexual Health Risk

Abstract: Purpose Our aim was to examine mechanisms underlying the development of sexual health risk behaviors in sexual minority girls (SMGs) and the relation of these mechanisms and sexual risk behaviors to sexual victimization. Methods Data were drawn from the Project on Human Development in Chicago Neighborhoods cohorts aged 15 and 18 (N = 391; 54 SMGs). Results SMGs reported more sexual victimization and steeper positive trajectories of substance misuse over time than heterosexual girls. Growth in alcohol use d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…Early substance use precedes or is associated with sexual initiation in adolescent males (Capaldi, Kerr, Owen, & Tiberio, 2017;Doran & Waldron, 2017;Epstein et al, 2014;Floyd & Latimer, 2010) and females (Cavazos-Rehg et al, 2012;Dillon et al, 2010;Doran & Waldron, 2017;Epstein et al, 2014;Floyd & Latimer, 2010) as well as African American (Kaplan et al, 2013;McGuire, Wang & Zhang, 2012;Turner, Latkin, Sonenstein, & Tandon, 2011) and Latino youth (Dillon et al, 2010;Kaplan et al, 2013). Numbers of sexual partners increases as alcohol (Epstein et al, 2014;Green et al, 2017;Oshri et al, 2014;Riggs et al, 2013;Vasilenko & Lanza, 2014), marijuana (Cavazos-Rehg et al, 2011;Floyd & Latimer, 2010;Green et al, 2017;Oshri et al, 2014) or smoking (Cavazos-Rehg et al, 2011;Demissie et al, 2017;McGuire, Wang & Zhang, 2012;Vasilenko & Lanza, 2014) use increases. However, alcohol use was not associated with number of sexual partners among a national representative sample of youth (Floyd & Latimer, 2010).…”
Section: Substance Use and Sexual Behaviorsmentioning
confidence: 99%
“…Early substance use precedes or is associated with sexual initiation in adolescent males (Capaldi, Kerr, Owen, & Tiberio, 2017;Doran & Waldron, 2017;Epstein et al, 2014;Floyd & Latimer, 2010) and females (Cavazos-Rehg et al, 2012;Dillon et al, 2010;Doran & Waldron, 2017;Epstein et al, 2014;Floyd & Latimer, 2010) as well as African American (Kaplan et al, 2013;McGuire, Wang & Zhang, 2012;Turner, Latkin, Sonenstein, & Tandon, 2011) and Latino youth (Dillon et al, 2010;Kaplan et al, 2013). Numbers of sexual partners increases as alcohol (Epstein et al, 2014;Green et al, 2017;Oshri et al, 2014;Riggs et al, 2013;Vasilenko & Lanza, 2014), marijuana (Cavazos-Rehg et al, 2011;Floyd & Latimer, 2010;Green et al, 2017;Oshri et al, 2014) or smoking (Cavazos-Rehg et al, 2011;Demissie et al, 2017;McGuire, Wang & Zhang, 2012;Vasilenko & Lanza, 2014) use increases. However, alcohol use was not associated with number of sexual partners among a national representative sample of youth (Floyd & Latimer, 2010).…”
Section: Substance Use and Sexual Behaviorsmentioning
confidence: 99%
“…Compared to their heterosexual peers, sexual minority girls (Brewster & Tillman, 2012; Oshri, Handley, Sutton, Wortel, & Burnette, 2014; Talley, Hughes, Aranda, Birkett, & Marshal, 2014) and women (Ford & Soto-Marquez, 2016; Johnson, Matthews, & Napper, 2016; Martin, Fisher, Warner, Krebs, & Lindquist, 2011; Murchison, Boyd, & Pachankis, 2016; Satinsky & Jozkowski, 2014) report greater sexual victimization. A limitation of much of the previous research is that bisexual and lesbian girls/women have been combined into a single category (e.g., Martin et al, 2011; Oshri et al, 2014; Rothman, Exner, & Baughman, 2011). Thus, important variation between sexual minority women has been ignored in order to make general statements about all sexual minority women as a whole.…”
Section: Sexual Coercion and Alcohol Use Among Bisexual Womenmentioning
confidence: 99%
“…As the inhibiting effects of alcohol or expectancies about the effects of alcohol on sex may increase engagement in risky sexual behaviors for youth in general (Cooper, 2002), it is anticipated that heavy alcohol involvement in response to minority stress would similarly play a role. In line with this hypothesis, a recent longitudinal study followed SMGs and their heterosexual counterparts from mid-adolescence to their mid-20s, and found that SMGs reported more sexual partners than female heterosexual youth, and that this disparity was partly explained by greater alcohol use among SMGs (Oshri, Handley, Sutton, Wortel, & Burnette, 2014). Thus, it appears that victimization may place SMGs at risk for both alcohol use as well as certain sexual behaviors.…”
mentioning
confidence: 92%